Korelasi Antara Minat dan Prestasi Belajar Sejarah Terhadap Kesadaran Sejarah Siswa di Kelas XI SMA Plus Darul Hikmah Al-Ghazaalie Tahun Ajaran 2024-2025 - Abd. Rosyid; Adzkiyak; Agi Ma’ruf Wijaya (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to determine the relationship between learning interest and history learning achievement towards the historical awareness of class XI students of SMA Plus Darul Hikmah Al-Ghazaalie in the 2024–2025 academic year. The method used is a quantitative approach with a correlational design. The study population was all class XI students, with a sampling technique using simple random sampling. Data were collected through a questionnaire to measure learning interest and historical awareness, as well as documentation of values ​​for learning achievement. Data analysis was carried out using Pearson Product Moment correlation and multiple regression analysis. The results showed that there was a positive and significant relationship between learning interest and students' historical awareness. Likewise, history learning achievement has a positive and significant correlation with historical awareness. Simultaneously, interest and achievement in learning history contribute significantly to increasing students' historical awareness. These findings emphasize the importance of strengthening interest and academic achievement in history learning to form better historical awareness among students.